2022
DOI: 10.1186/s12893-022-01729-2
|View full text |Cite
|
Sign up to set email alerts
|

Severe hyperlactatemia in unselected surgical patients: retrospective analysis of prognostic outcome factors

Abstract: Background Etiology of hyperlactatemia in ICU patients is heterogeneous—septic, cardiogenic or hemorrhagic shock seem to be predominant reasons. Multiple studies show hyperlactatemia as an independent predictor for ICU mortality. Only limited data exists about the etiology of hyperlactatemia and lactate clearance and their influence on mortality. The goal of this single-center retrospective study, was to evaluate the effect of severe hyperlactatemia and reduced lactate clearance rate on the out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…It was observed that nonsurvivors presented with higher lactate levels at 0, 6th, and 12th hours compared to survivors. This result indicates a potential association between elevated lactate and adverse outcomes, similar to those observed in prior studies (11)(12)(13). The observed pattern of hyperlactatemia frequency over the rst 24 hours, with a decline from 64-36%, indicates the dynamic nature of lactate levels in this population.…”
Section: Discussionsupporting
confidence: 85%
“…It was observed that nonsurvivors presented with higher lactate levels at 0, 6th, and 12th hours compared to survivors. This result indicates a potential association between elevated lactate and adverse outcomes, similar to those observed in prior studies (11)(12)(13). The observed pattern of hyperlactatemia frequency over the rst 24 hours, with a decline from 64-36%, indicates the dynamic nature of lactate levels in this population.…”
Section: Discussionsupporting
confidence: 85%
“…These studies have demonstrated that serum lactate levels hold a crucial role in risk-stratification in critically ill patients. It is reported during the initial stage of treatment, lactate levels seem to be more closely associated with the outcome compared to frequently measured parameters such as oxygen delivery and oxygen consumption [ 3 , 4 , 8 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, these studies only analyzed one to two months of data and retrieved data from a single site in different places, which were New York or the Alborz province in Iran [11,12]. Furthermore, hyperlactatemia has traditionally been a marker of poor prognosis in critically ill patients [13]. In our study, ESRD patients had 3.19 higher odds for having elevated lactate levels and 2.12 higher odds for ≥ 7 days of hospital stay.…”
Section: Analysis Of Propensity Matched Samplesmentioning
confidence: 89%
“…Furthermore, hyperlactatemia has traditionally been a marker of poor prognosis in critically ill patients [ 13 ]. In our study, ESRD patients had 3.19 higher odds for having elevated lactate levels and 2.12 higher odds for ≥ 7 days of hospital stay.…”
Section: Discussionmentioning
confidence: 99%